PENERAPAN STANDAR AKUNTANSI PEMERINTAH, TEKNOLOGI INFORMASI, PENGENDALIAN INTERN, DAN MOTIVASI KERJA TERHADAP KUALITAS LAPORAN KEUANGAN - Meliana Rahmawati; Rina Trisnawati (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2021)
This study analyzes the effect of applying government accounting standards, the use of information technology, internal control systems, and work motivation on the quality of financial reports. The sample in this study was 19 Dinas in the Boyolali Regency. Methods of data collection by using a questionnaire to 52 respondents from the finance department. The sampling technique used was convenience sampling with a questionnaire. The data analysis technique used to test the hypothesis in this study is multiple linear regression analysis with the help of the SPSS program. This study indicates that government accounting standards, the use of information technology, and work motivation do not affect the quality of financial reports, while the internal control system affects the quality of financial reports.